Edukasi Cuci Tangan dengan Sabun pada Siswa SDIT Lukmanul Hakim - Lahay, Sitty Fadhilla Fitrianty; Iman, Dian Pratiwi; Anita, Astri - (Universitas Negeri Gorontalo, 2025)
Hand hygiene remains one of the essential factors influencing the health of school-aged children, who are particularly vulnerable to infectious diseases. Handwashing with soap (HWWS) is a simple yet highly effective measure in preventing the transmission of various illnesses. This community service program aimed to enhance the knowledge, awareness, and handwashing practices of second-grade students at SD IT Lukmanul Hakim, Limboto District, Gorontalo Regency. The activity was conducted on September 19, 2025, involving 26 students. The educational methods included material presentation, educational video screening, demonstration of proper handwashing steps, and interactive games using visual worksheets to strengthen students’ understanding. The results indicated that students participated enthusiastically, actively asked questions, and were able to correctly demonstrate the handwashing steps. The use of video media and interactive games proved effective in increasing comprehension and making the learning process more engaging and accessible for children. Overall, this program successfully promoted clean and healthy living behaviors among students, particularly in encouraging handwashing with soap as part of their daily routine.